Strategic Business Management Analysis Implemented by Marriott International Lodging Companies - Chanda Vedalla Putra; Charles Tan; Jason Jason; Johanes Prawira; Ng Thian Way (Universitas Muhammadiyah Makassar, 2023)
This article revolves around the hospitality industry and Marriott International, a hospitality company based in the United States. With a wide array of properties and brands spanning 74 countries globally, Marriott International boasts an expansive presence. The primary focus of this article is to analyze the strategic management efforts undertaken by Marriott Hotels. Marriott employs numerous strategic management processes crucial for thriving within the fiercely competitive hospitality sector. Furthermore, this article delves into an examination of Marriott's internal and external environment, along with an exploration of the competitive dynamics inherent in the hospitality industry's market competition. The author utilizes qualitative research methods, complemented by a descriptive approach and an extensive literature review, to gather relevant information pertinent to this subject. This article underscores the allure of the hospitality business, highlighted by its elevated economies of scale, significant switching costs, and the diminished bargaining power held by both customers and suppliers. However, the hospitality business is not without its drawbacks. Notably, a substantial threat emerges from substitute products, underscoring a disadvantage that cannot be disregarded.